Production of Prebiotic Xylooligosaccharides via Dilute Maleic Acid-Mediated Xylan Hydrolysis Using an RSM-Model-Based Optimization Strategy - Jiang, Kankan; Fu, Xiaoliang; Huang, Rong; Fan, Xingli; Ji, Lei; Cai, Damin; Liu, Xiaoxiang; Fu, Yixiu; Sun, Aihua; Feng, Chenzhuo (Frontiers in Nutrition, 2022)
Xylooligosaccharides (XOS) are functional feed additives that are attracting growing commercial interest owing to their excellent ability to modulate the composition of the gut microbiota. The acid hydrolysis-based processing of xylan-containing materials has been proposed to represent a cost-effective approach to XOS preparation, with organic acids being preferable in this context. As such, in the present study, maleic acid was selected as a mild, edible organic acid for use in the hydrolysis of xylan to produce XOS. A response surface methodology (RSM) approach with a central composite design was employed to optimize maleic acid-mediated XOS production, resulting in a yield of 50.3% following a 15 min treatment with 0.08% maleic acid at 168℃. Under these conditions, the desired XOS degree of polymerization (2-3) was successfully achieved, demonstrating the viability of this using a low acid dose and a high reaction temperature to expedite the production of desired functional products. Moreover, as maleic acid is a relatively stable carboxylic acid, it has the potential to be recycled. These results suggest that dilute maleic acid-based thermal treatment of corncob-derived xylan can achieve satisfactory XOS yields, highlighting a promising and cost-effective approach to XOS production.